Fracture of the neck of an uncemented femoral component unrelated to trunnion corrosion - Jonathan R. Peterson, MD; Timothy M. Wright, PhD; Samuel S. Wellman, MD; Paul F. Lachiewicz, MD (Arthroplasty Today, 2019)
This is the first report, to our knowledge, of a fracture, unrelated to trunnion corrosion, through the midneck of a well-fixed uncemented cobalt-chromium alloy femoral component that had been implanted via a total hip revision arthroplasty 25 years ago. Three years after a second revision for polyethylene wear, the patient noted an acute onset of pain in the left hip. There was no antecedent pain in the hip or thigh. Radiographs and intraoperative findings showed a well-fixed femoral component. Electron microscopic retrieval analysis showed intergranular material cracks. Revision of the femoral component was performed with an extended trochanteric osteotomy. This fracture of the femoral component neck was likely related to metal fabrication techniques, and surveillance of this component may be warranted. Keywords: Femoral component neck fracture, Total hip arthroplasty, Revision, Catastrophic failure